2007
DOI: 10.1111/j.1540-8175.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension and Left Heart Function: Insights from Tissue Doppler Imaging and Myocardial Performance Index

Abstract: The result infers that the systolic and diastolic function of LV declined, following pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…Besides, it is conceivable that, in patients with more severe PH, aortic size can diminish, due to a corresponding reduction in cardiac output [15].…”
Section: Discussionmentioning
confidence: 98%
“…Besides, it is conceivable that, in patients with more severe PH, aortic size can diminish, due to a corresponding reduction in cardiac output [15].…”
Section: Discussionmentioning
confidence: 98%
“…Recent data, using MPI, have suggested that alterations in both LV systolic and diastolic function occur as a result of cPH [31]. Specifically, prolongation of the LV-IVRT interval, indicative of LV diastolic dysfunction, has been shown in patients with moderate or worse degrees of cPH, irrespective of their PH etiology [31]; as well as evidence of global LV systolic and diastolic impairment in patients with Fig. 3 Box plot showing differences between Group I and II with regards to heart rate corrected duration of mitral annular systole and diastole chronic obstructive pulmonary disease with PH [13].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, these conformational changes in terms of both RV hypertrophy and dilatation are thought to impair LV distensibility, causing LV diastolic dysfunction [10]. Recent data, using MPI, have suggested that alterations in both LV systolic and diastolic function occur as a result of cPH [31]. Specifically, prolongation of the LV-IVRT interval, indicative of LV diastolic dysfunction, has been shown in patients with moderate or worse degrees of cPH, irrespective of their PH etiology [31]; as well as evidence of global LV systolic and diastolic impairment in patients with Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental findings and clinical observations suggest that elevated mPAP cannot be the single driver for RV failure [62], therefore, targeting the RV may be a promising approach [6]. As for the LV myocardium, echocardiography shows compromised LV function in various aetiologies of PH [67], mainly due to ventricular interdependence and impaired filling [68]. Nevertheless, myocardial abnormalities partly underlie LV dysfunction.…”
Section: The Rv In Phmentioning
confidence: 99%